Impact of Nodulation Efficiency and Concentrations of Soluble Sugars and Ureides on Soybean Water Deficit During Vegetative Growth - Helena Chaves Tasca; Douglas Antônio Posso; Altemir José Mossi; Cimélio Bayer; Rogério Luís Cansian; Geraldo Chavarria; Tanise Luisa Sausen (Nitrogen)
Drought is the primary limiting factor affecting soybean productivity, and is exacerbated by climate change. In legumes like soybeans, biological nitrogen fixation (BNF) is the main form of nitrogen acquisition, with nitrogen being converted into ureides. A greenhouse experiment was conducted using the soybean cultivar BMX Zeus IPRO, with two water treatments applied during the vegetative phase: control (C) and water deficit (D). The relative water content and number of nodules were reduced in the D plants. Ureide concentrations (allantoin and allantoic acid) were higher in nodules under D conditions. However, no differences were observed in allantoin, total ureide, and soluble sugar concentrations in leaves. Our results suggest that reducing the number of nodules may be a key strategy for maintaining BNF under drought conditions and that ureide accumulation could be the primary metabolic response in this soybean cultivar. These findings indicate that the effects of water restriction on BNF are likely associated with local metabolic responses rather than a systemic ureide feedback mechanism inhibiting BNF.